Correlação entre o volume tomográfico e a avaliação histopatológica de lesões perirradiculares - Silva, Raí de Almeida da (2016)
Pulp necrosis of the root canal system stimulates an inflammatory response in the periapical region. Apical chronic periodontitis are divided histologically in granulomas or periradicular cysts. Using a three-dimensional cone beam computed tomography for volumetric measurements obtained by differences in radiographic density, this study correlates the volume of apical lesions and the histopathologic diagnosis of granulomas or periradicular cysts, and established a protocol to measure volume of apical lesion by CBCT. Twenty-four biopsies (n CAEE. 0072.0.317.000-10), subdivided into granulomas or periradicular cysts (n = 12) each had CT scans analyzed volumetrically through the Software Amira (FEI Company, Oregon, USA). There was a large difference between the average volumes for each pathology. The great variation in the cyst group shows the cyst size variability among the patients. The volumes of the granuloma and cysts were statistically analyzed using the Mann-Whitney test with significance level of 5%, (p = 0.01), demonstrating a statistically significant difference between the mean volumes of the lesion in each pathology. Within the limitations of a small sample, the findings of this study show that cysts have statistically higher volume compared to granulomas and a protocol of the volumetric measurement of apical lesion was established.